Evaluation of the antimicrobial effectiveness of Propolis medicaments within the root canals that infected with Enterococcus faecalis (Journal of Hama University, 2022)
Bacteria and their products play an essential role in the initiation and persistence of endodontic and periodontal diseases. Among the bacteria that cause the disease in the root canals is Enterococcus faecalis,this research aims to study the ability of(*calcium hydroxide-saline paste ,*calcium hydroxide-propolis paste) as addressing in eliminating E.faecalis bacteria inside the infected root canals.20 extracted single rooted human premolars with single canals were prepared after cutting their crowns in order to standardize the root length measurement to 17 mm and then randomly distributed into two equal groups , group 1(n=10) calcium hydroxide 1g -1.5ml saline ,group 2(n=10) calcium hydroxide 1g- 2ml propolis.Each canal was injected with the prepared bacterial suspension , which was incubated aerobically inside the incubator at 37° and the samples were left inside the incubator for 7 days. The units forming the bacterial colonies were counted before and after the application of the irrigation protocol with Naocl. Then the samples were stuffed with the appropriate paste and incubated for 7 days in the presence of moisture.then count the units forming the bacterial colonies.The value of the T- Student test for studying the differences in the number of Enterococcus faecalis in the stage after applying the dressings between the group of calcium hydroxide -saline paste and the group of calcium hydroxide -propolis paste was (2.192), and its P value was (0.042), which is smaller than the level of Significance (0.05), and this indicates that there is a statistically significant difference between the two studied groups. This statistically significant difference is in favor of the calcium hydroxide -propolis paste group.